2014
DOI: 10.14740/jocmr1675w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Neuropathic Pain at the Population Level

Abstract: BackgroundOne of the chief complaints of individuals who frequent the Family Health Units is chronic pain which, in Salvador, affects over 40% of the population. However, little is known about the type of pain and its impact on quality of life (QoL) at population level. The aim of the study is to evaluate the impact of neuropathic pain on QoL in a community.MethodsA descriptive cross-sectional study was conducted from March to October 2012, in a Family Health Unit, Salvador, Bahia, Brazil. The DN-4 (type of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…If diagnosed of CPSP, a douleur neuropathic 4-questionnaire (DN-4) was followed to ascertain whether the pain was a neuropathic Pain (NP). DN-4 is an instrument evaluating pain characteristics through 10 items, total score being 10 [ 9 , 10 ]. If the patient score is ≥ 4, neuropathic pain is diagnosed.…”
Section: Methodsmentioning
confidence: 99%
“…If diagnosed of CPSP, a douleur neuropathic 4-questionnaire (DN-4) was followed to ascertain whether the pain was a neuropathic Pain (NP). DN-4 is an instrument evaluating pain characteristics through 10 items, total score being 10 [ 9 , 10 ]. If the patient score is ≥ 4, neuropathic pain is diagnosed.…”
Section: Methodsmentioning
confidence: 99%
“…48,56 Indeed, pain affects 20% to 40% of the general population in Latin America (LA) and constitutes a major public health challenge. 39,88,92,93,112 The most frequent pain syndromes are osteoarthritis-related pain, low back pain (LBP), headaches, and neuropathic pain syndromes. 2,5,39,40,92,93,95 For instance, the lifetime prevalence of acute LBP is close to 70%, and it has been suggested that more than half will eventually experience chronification, 12,47 ranking chronic LBP as the first cause of years lived with disability 80,114 worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, few studies have examined the prevalence of NeP in Brazil or examined NeP-related outcomes. Those studies that do exist have reported NeP estimates of 60% among those with chronic pain11 and 10% among the general population 12. Additionally, there does not appear to be any studies reporting the impairment associated with specific NeP etiologies.…”
Section: Introductionmentioning
confidence: 99%